(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2020)
In the present study, antibiogram of Escherichia coli isolated from farmed Asian clam, Corbicula fluminea was characterised. Asian clam or locally known as ‘etak’ is processed to became smoked clam and consumed as snack by Kelantanese. However, there are many diarrhoea cases after consuming smoked clam. Furthermore, there are also insufficient information about the E.coli level in Asian clam farm and effective antibiotic in controlling the bacteria in the litereature. Hence, this study was carried out to provide information of antibiogram of E.coli to be reference in the future. Eosin Methylene Blue agar (EMB) was used to isolate E. coli. A total of 100 isolated bacteria were subjected to antibiotic sensitivity test using disk diffusion method. A total of 18 types of antibiotics namely novobiocin (30µg/disk), fosfomycin (50 µg/disk), tetracycline (30µg/disk), lincomycin (15µg/disk), flumequine (30µg/disk), sulphamethoxazole (25 µg/disk), amoxycillin (25 µg/disk), chloramphenicol (30 µg/disk), oleandomycin (15 µg/disk), spiramycin (100 µg/disk), ampicillin (10 µg/disk), oxytetracycline (30 µg/disk), doxycycline (30 µg/disk), nalidixic acid (30 µg/disk), florfenicol (30 µg/disk), erythromycin (15 µg/disk), kanamycin (30 µg/disk) and oxolinic acid (2 µg/disk). The findings of the present study showed total plate count of E. coli was 6.45 x 103 colony forming unit (CFU/100g) of sampled Asian clam. Hence, the clam is needed to be under cleansing treatment before can consider safe for human consumption. Antibiotic results showed 51 % was recorded as antibiotic resistance case, 44 % antibiotic sensitive case and 5 % as antibiotic intermediary sensitive case. None of the tested antibiotics was successfully inhibited the growth of the present bacterial isolates indicating more antibiotics are needed to be screen in the future study to find out the most effective antibiotic in controlling isolated E. coli.